Investigating emotions in Parkinson's disease: what we know and what we still don't know - Sotgiu, Igor; Rusconi, Maria Luisa (Frontiers in Psychology, 2013)
Over the last decade, there has been an increasing attention to the role played by emotional processes in Parkinson’s disease. However, most of what is known in this area is based on research conducted in laboratory or clinical settings. In this article, the authors underline the need to expand our current knowledge of the psychological correlates of Parkinson’s disease by investigating patients’ everyday emotions in natural contexts. Specifically, the authors illustrate new research avenues based on the implementation of experience sampling methods. It is argued that these methods could permit future researchers to ecologically assess the frequency and intensity with which parkinsonian patients experience specific emotions (either negative or positive) during their everyday life, providing at the same time precious information on what are the most typical situations in which these emotions occur and on how patients behave in these circumstances. Potential practical implications associated with investigating these issues are discussed.